Unique Structural Features of Membrane-Bound C-Terminal Domain Motifs Modulate Complexin Inhibitory Function - Snead, David; Lai, Alex L.; Wragg, Rachel T.; Parisotto, Daniel A.; Ramlall, Trudy F.; Dittman, Jeremy S.; Freed, Jack H.; Eliezer, David (Frontiers in Molecular Neuroscience, 2017)
Complexin is a small soluble presynaptic protein that interacts with neuronal SNARE proteins in order to regulate synaptic vesicle exocytosis. While the SNARE-binding central helix of complexin is required for both the inhibition of spontaneous fusion and the facilitation of synchronous fusion, the disordered C-terminal domain (CTD) of complexin is specifically required for its inhibitory function. The CTD of worm complexin binds to membranes via two distinct motifs, one of which undergoes a membrane curvature dependent structural transition that is required for efficient inhibition of neurotransmitter release, but the conformations of the membrane-bound motifs remain poorly characterized. Visualizing these conformations is required to clarify the mechanisms by which complexin membrane interactions regulate its function. Here, we employ optical and magnetic resonance spectroscopy to precisely define the boundaries of the two CTD membrane-binding motifs and to characterize their conformations. We show that the curvature dependent amphipathic helical motif features an irregular element of helical structure, likely a pi-bulge, and that this feature is important for complexin inhibitory function in vivo.